RISK FACTORS FOR SUICIDAL BEHAVIOR IN AFFECTIVE DISORDERS IN ADULTS AND ADOLESCENTS - Sh. J. Jurayev (Zeta Repository, 2023)
This article states that currently suicide attempts and suicides among adults and adolescents are a common and serious global clinical problem and a public health problem. health care among psychiatric hospital patients. It was mentioned that the identification of risk factors for certain types of major affective disorders can help in determining the risk of suicide, supporting preventive measures and treating patients from risks and improving prognosis. In particular, bipolar disorders and depressive disorders have a particularly high risk of mental illness.